2015
DOI: 10.7717/peerj.1195
|View full text |Cite
|
Sign up to set email alerts
|

Personality and intelligence: persistence, not self-directedness, cooperativeness or self-transcendence, is related to twins’ cognitive abilities

Abstract: Background. A person-centered approach focusing on the interaction of an individual’s temperament-character-life events is essential in the path of individuals’ well-being. In this context, three character traits, Self-directedness (e.g., self-acceptance, self-control, goal-directed behavior), Cooperativeness (e.g., social affiliation, social tolerance, empathy and helpfulness) and Self-transcendence (e.g., spiritual acceptance, transpersonal identification), measured using Cloninger’s model of personality are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…The similarities may be attributed in part to the selection processes and the universal requirement of high academic standards. [28][29][30] Additionally, self-selection into dentistry may attract students with similar traits. It is more likely is that higher levels of Self-Transcendence in international students are due to cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities may be attributed in part to the selection processes and the universal requirement of high academic standards. [28][29][30] Additionally, self-selection into dentistry may attract students with similar traits. It is more likely is that higher levels of Self-Transcendence in international students are due to cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Temperament and Character Inventory (Cloninger et al, 1993 ) researchers have found that Self-directedness (i.e., agency), Cooperativeness (i.e., communion), and Self-transcendence (i.e., Spirituality) are associated to high levels of happiness, psychological well-being, and less violent behavior (Garcia et al, 2013 , 2015 ; Nima and Garcia, 2015 ; Mousavi et al, 2015 ). Moreover, low Self-directedness and Cooperativeness is recurrent among individuals with all types of mental health problems, such as, depression, schizophrenia, anxiety disorder, autism spectrum disorders, attention deficit/hyperactivity disorder, and etcetera.…”
mentioning
confidence: 99%
“…For example, while the character scales do not show common environmental influences in research among older adults (e.g., Gillespie et al 2003), a small common environmental influence for self-directedness and cooperativeness has been found among young adults (20-30 years of age; e.g., Ando et al 2004). In addition, recent research using one of the largest population-based-twin-studies among adolescents, found suggestive evidence of common environmental influence for all of the character scales Mousavi et al 2015). In sum, the genetic structure of character scales in the adolescent sample shows a modest but noteworthy proportion of shared environmental influence that is not present in adult samples.…”
Section: Limitations Strengths and Future Researchmentioning
confidence: 91%
“…What is more, there is TCI normative data in 22 countries (e.g., USA, Sweden, Japan, China, Mexico, Italy) on four continents (North and South America, Europe, Asia, Oceania) showing that the factor structure is identical around the world and also data on age appropriate norms showing that the same dimensions are present across the lifespan as well (C. R. Cloninger, personal communication, June 10, 2015; see also Josefsson et al 2013). The TCI is sensitive to reading level, but for a forthcoming adolescent and adult short version, there was no need to change wording (C. R. Cloninger, personal communication, June 10, 2015; see also the non-significant association between TCI dimensions and cognitive ability among adolescent twins in Mousavi et al 2015). Hence, suggesting that the TCI can be used among adolescents to measure agentic, communal, and spiritual traits.…”
Section: Introductionmentioning
confidence: 99%